The German army and counterinsurgency in Afghanistan: The need for strategy - Thomas Noetzel; Benjamin Schreer (Stiftung Wissenschaft und Politik (SWP), 2008)
Alongside their NATO allies German troops are facing a growing insurgency in Afghanistan. However, the alliance still lacks a joint strategy to deal with this challenge. While the US government recently called on NATO to pursue a 'classical' counterinsurgency campaign, Germany insisted on the development of a more 'comprehensive strategy' before the next Summit in Bucharest in April 2008. Yet, over recent months the German position has been criticized by a range of allies for lack of credibility. To gain political influence over the making of NATO's Afghanistan strategy, the German government first needs to adjust its national position on how to deal with the Afghan insurgency
Keywords: 320